Integrating Oxaliplatin with Highly Luminescent Carbon Dots: An Unprecedented Theranostic Agent for Personalized Medicine. (14th March 2014) - Zheng, Min; Liu, Shi; Li, Jing; Qu, Dan; Zhao, Haifeng; Guan, Xingang; Hu, Xiuli; Xie, Zhigang; Jing, Xiabin; Sun, Zaicheng
<x xml:space="preserve">Abstract</x> A theranostic nanomedicine (CD‐Oxa) is synthesized by means of the condensation reaction between the amino groups on the surface of fluorescent carbon dots (CDs) and the carboxyl group of the oxaliplatin derivative Oxa(IV)‐COOH. CD‐Oxa, which integrates the optical properties of CDs and the anticancer function of oxaliplatin, could be used for simultaneous drug delivery and fluorescent tracking. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>